Expression Analysis of Glucocorticoid Hormone During Early Developmental Stage of Zebrafish (Danio rerio) its Therapeutic Implications (Bangladesh Pharmaceutical Journal, 2015)
Glucocorticoid is prescribed for the treatment of many human diseases. The work was performed to investigate the role of glucocorticoid hormone on the gene expression during zebrafish (Danio rerio) embryogenesis. Microarray hybridization technique was used to analyse dys-regulation of different gene expression at 12 hours post fertilization (hpf) when single cell fertilized eggs were treated with glucocorticoid hormone. The expression of 149 genes were affected, with 143 up-regulated and 6 down-regulated. The results suggest that glucocorticoid may be also used in therapeutic approach to change genetic expression at early developmental stage. DOI: http://dx.doi.org/10.3329/bpj.v17i1.22316 Bangladesh Pharmaceutical Journal 17(1): 55-61, 2014